Solution‐processed high‐k oxide dielectric via deep ultraviolet and rapid thermal annealing for high‐performance MoS2 FETs. Issue 1 (7th September 2016) - Yoo, Geonwook; Choi, Sol Lea; Yoo, Byungwook; Oh, Min Suk
Abstract : So far most of MoS2 ‐based devices have been demonstrated on oxide gate dielectrics (e.g., SiO2, Al2 O3, HfO2, etc) deposited by vacuum process or on polymer gate dielectrics. In this study, we report electrical characteristics of multilayer MoS2 transistors fabricated on solution‐processed high‐ k AlO x gate dielectric via deep ultraviolet (DUV) activation in combination with rapid thermal annealing process at 250 °C. The solution‐processed AlO x sol–gel film exhibited low leakage current of about 1.49 μA cm −2 at 1 MV cm −1 and a relative dielectric constant ( k ) of ∼6.1 at 1 kHz. The fabricated MoS2 ‐FETs exhibit median field‐effect mobility of ∼23.3 cm 2  V −1 s −1, threshold voltage of ∼ 0.79 V, subthreshold slope of ∼0.30 V dec −1, and on/off current ratio of ∼10 7 . The electrical performance can be further improved by optimizing the AlO x sol–gel film as well as the device structure, and the result implies that the solution‐processed high‐ k AlO x is promising for TMDC–based device applications.